2019
DOI: 10.1080/07315724.2019.1683379
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s Disease and Parkinson’s Disease: A Nutritional Toxicology Perspective of the Impact of Oxidative Stress, Mitochondrial Dysfunction, Nutrigenomics and Environmental Chemicals

Abstract: Introduction: Alzheimer's disease is primarily a dementia-related disorder from progressive cognitive deterioration and memory impairment, while Parkinson's disease is primarily a movement disorder illness having movement disorder symptoms, bradykinesia (slowness of movements), hypokinesia (reduction of movement amplitude), and akinesia (absence of normal unconscious movements) along with muscle rigidity and tremor at rest. While aging is the main risk factor, epidemiological evidence suggests that the exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(60 citation statements)
references
References 89 publications
0
56
0
4
Order By: Relevance
“…If these processes become uncoordinated, mitochondrial dysregulation can ensue. Hence, mitochondrial dysfunction is causative in many human ailments, including neurological abnormalities [40, 41]. It is important to investigate common phenotypes between human and animal models of CS to explore conserved pathways.…”
Section: Discussionmentioning
confidence: 99%
“…If these processes become uncoordinated, mitochondrial dysregulation can ensue. Hence, mitochondrial dysfunction is causative in many human ailments, including neurological abnormalities [40, 41]. It is important to investigate common phenotypes between human and animal models of CS to explore conserved pathways.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 NDDs like PD, AD and, HD can result in dementia and depression and thus contribute to elevated mortality and morbidity, (disabilities) which pose an enormous economical burden. 3 , 4 Also, NDDs are highly connected to aging, and hence the prevalence rate is higher in older people than young owing to decline or altered hormone secretion, enhanced oxidative stress, and, neuro-inflammation. Several studies also demonstrated that NDDs have a direct impact on the social-economic status of any community or country as it hampers cognition and physical (unhealthy aging) or motor movement (quality of life) as well as an incurable condition.…”
Section: Introductionmentioning
confidence: 99%
“…Although AD is not curable, some treatments are available to slow down the disease progression and reduce the cognitive impairment and behavioural problems, but do not stop the progression of neurodegeneration [ 38 ]. Our research may show new details about Aβ aggregation and fibrillation associated with AD and highlight the role of aluminium ions in creating a hydrophobic environment that increases the tendency of Aβ peptides to form plaques in AD brains.…”
Section: Discussionmentioning
confidence: 99%